2006
DOI: 10.1520/jai13430
|View full text |Cite
|
Sign up to set email alerts
|

Spent Fuel Monitoring with Silicon Carbide Semiconductor Neutron/Gamma Detectors

Abstract: Silicon carbide semiconductor radiation detectors have been demonstrated for neutron and gamma-ray monitoring of spent nuclear fuel. Neutrons and gamma rays were monitored simultaneously over a 2050-h period, resulting in a gamma dose of over 6000 Gy to the SiC detector. No changes in the neutron and gamma-ray sensitivity were observed as a result of the gamma-ray exposure. After the spent-fuel measurements, the absolute neutron sensitivity was determined in a standard neutron field, and the degree of gamma-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Long-term monitoring carried out over a 2050 hour period and a total gamma-ray dose to the detector of over 6000 Gy did not induce gain drifts in the detector [20]. This is still a limited test in terms of total neutron fluence but is nevertheless encouraging for performing more extensive tests of SiC detectors in a high neutron flux environment.…”
Section: Pos(ifd2015)008mentioning
confidence: 76%
“…Long-term monitoring carried out over a 2050 hour period and a total gamma-ray dose to the detector of over 6000 Gy did not induce gain drifts in the detector [20]. This is still a limited test in terms of total neutron fluence but is nevertheless encouraging for performing more extensive tests of SiC detectors in a high neutron flux environment.…”
Section: Pos(ifd2015)008mentioning
confidence: 76%
“…Such severe environments can be encountered in terrestrial [8] and space [3] nuclear reactor applications as well as in spent reactor fuel monitoring applications [9,10]. Natsume et al [10] showed that the gamma and neutron response efficiencies for a SiC Schottky diode were unchanged during and following a 2050-h exposure to spent nuclear fuel resulting in an estimated 6-kGy gamma-ray exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Natsume et al [10] showed that the gamma and neutron response efficiencies for a SiC Schottky diode were unchanged during and following a 2050-h exposure to spent nuclear fuel resulting in an estimated 6-kGy gamma-ray exposure. The present work indicates that the SiC detector would continue to operate for greater than 200 years in a similar spent-fuel measurement environment.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that SiC radiation detector response is highly linear for neutron and gamma rays and highly feasible for harsh high-temperature and high-radiation environments [7][8][9]. Generally neutrons are measured with a semiconductor detector with neutron convertors such as 6 Li or 10 B.…”
Section: Introductionmentioning
confidence: 99%